Harvest season and head rice yield of upland rice cultivars submitted to parboiling - Garcia, Diva Mendonça; Caliari, Márcio; Fonseca, Flávia Araújo da; Soares Júnior, Manoel Soares; Bassinello, Priscila Zaczuk (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2012)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]–> This work aimed to evaluate the effects of parboiling on the yield of upland rice cultivars harvested at different times. The cultivars were BRS Primavera and BRS Sertaneja, harvested at 30 and 47 days after flowering (DAF). For parboiling, samples were soaked in water bath at 65 °C in grain: water ratio of 1:1.6 in order to reach 25% and 30% moisture, and then were autoclaved for 10 minutes at 120 °C and 1.1 kg/cm2 of pressure. After drying up to 13% moisture in a greenhouse with forced air at 40 °C, samples were benefited, followed by separation using the trieur equipment and weighing to obtain the head rice yield. The results showed a higher yield for head rice harvested at 30 DAF than at 47 DAF (BRS Primavera 63.2 and 38.7%; BRS Sertaneja 68.5 and 55.7%, respectively). Parboiling increased the head rice yield, regardless of harvest season, but partly reflected the potential of the cultivar origin: BRS Primavera 70.06%, BRS Sertaneja 74.94%. It is concluded that the harvest season is one of the factors that most influence the quality of industrial rice and the effect of parboiling also depends on the potential of the material source. <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif] –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>